2016
DOI: 10.1159/000445353
|View full text |Cite
|
Sign up to set email alerts
|

Macular Retinal Ganglion Cell Layer Thickness Is Not Reduced in Patients with Obstructive Sleep Apnea

Abstract: Purpose: To evaluate macular ganglion cell layer (GCL) and ganglion cell-inner plexiform layer (GCIPL) thicknesses in patients with obstructive sleep apnea (OSA) syndrome. Methods: 73 OSA patients and 67 age-matched controls were consecutively and prospectively enrolled. All participants underwent at least one reliable standard automated perimetry (SAP) and were imaged with spectral-domain optical coherence tomography (OCT) using two different devices. The OCT parameters were compared between groups, and Pears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“… 17 The fact that a tissue using up excessive oxygen such as cornea is quite probable to be consistently hypoxic in OSAS cases, though our study found no significant difference in corneal thickness between the groups. 6 , 18 , 19 However, in a study conducted by Koseoglu et al with 195 participants, corneal thickness decreased in OSAS group compared to the control group. Besides, similarly, they found that CCT was adversely associated with Oxygen Desaturation Index (ODI) values, desaturation rates, and decidedly related with least O 2 immersion values.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 17 The fact that a tissue using up excessive oxygen such as cornea is quite probable to be consistently hypoxic in OSAS cases, though our study found no significant difference in corneal thickness between the groups. 6 , 18 , 19 However, in a study conducted by Koseoglu et al with 195 participants, corneal thickness decreased in OSAS group compared to the control group. Besides, similarly, they found that CCT was adversely associated with Oxygen Desaturation Index (ODI) values, desaturation rates, and decidedly related with least O 2 immersion values.…”
Section: Discussionmentioning
confidence: 92%
“…At the point when the AHI is no less than 5 events/h, OSAS is viewed as a clinical substance. 6 It was reported that OSAS was essentially associated with a few neurodegenerative disorders, for example, Alzheimer’s disease, Parkinson disease. 7 - 9 Ophthalmological disorders such as non-arteritic anterior ischemic optic neuropathy (NAION), central serous retinopathy, floppy eyelid syndrome, primary open-angle glaucoma, normal tension glaucoma, and papilledema are in the reports of the patients who are suffering from the effects of OSAS.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited studies on ganglion cell thickness in patients with OSAS, which may lead to glaucoma and reduction in RNFL thickness. Ferrandez et al 37 showed that neither GC-IPL nor GCL thickness were reduced in OSAS patients compared with healthy controls. 37 Conversely, Huseyinoglu et al 30 found lower ganglion cell thickness in patients with severe OSAS compared to the control group.…”
Section: Discussionmentioning
confidence: 97%
“…Ferrandez et al 37 showed that neither GC-IPL nor GCL thickness were reduced in OSAS patients compared with healthy controls. 37 Conversely, Huseyinoglu et al 30 found lower ganglion cell thickness in patients with severe OSAS compared to the control group. In addition, there was a significant negative correlation between AHI and GC thickness.…”
Section: Discussionmentioning
confidence: 97%
“…7,[19][20][21][80][81][82][83][84] Studies of electrophysiology and RNFL thickness have reported conflicting findings in OSA patients, some showed significant reduction of the RNFL thickness, 9,19,21,71 pattern electroretinogram (PERG), 82,84 and visual evoked potential (VEP), 83,84 while others found no decrease [85][86][87] or alterations of ERG. 83 Our results did not show any reduction of RNFL thickness or VF in the OSA group, in agreement with previous studies by Salzgeber et al, 87 Ferrandez et al, 85,86 and Yu et al, 88 which did not find significant thinning of the RGC layer or macular thickness in OSA patients. Various authors have found affected values of MD and PSD in OSA patients, [89][90][91] and Ferrandez et al 85 have reported an impairment in the VF evaluated by SAP, suggesting dysfunction but not the death of the RGC.…”
Section: Discussionmentioning
confidence: 99%